Delibazione e divorzio nella giurisprudenza della Cassazione: il difficile bilanciamento tra attuazione della normativa concordataria e tutela del coniuge più debole (Stato, Chiese e pluralismo confessionale, 2024)
Exequatur procedure and divorce in the jurisprudence of the Supreme Court: the difficult balance between implementation of the concordat legislation and protection of the weaker spouseABSTRACT: The 1984 Agreement with the catholic church modified the rules for implementing canonical sentences of nullity of marriage in the Italian legal system, introducing several controls among wich the non-contradiction to Italian public order of such sentences has acquired increasing importance. In recent years, this requirement has been interpreted by the jurisprudence of the Supreme Court in a very restrictive manner in order to limit the recognition proceeding as much as possible, with the aim of avoiding the unfavorable economic consequences deriving from the nullity of the marriage for the spouse who would have been entitled to maintenance allowance in the event of divorce. The work focuses on the relationship between recognition of canonical nullity and divorce, analyzing the repeated interventions of the Court of Cassation to prevent that with the exequatur procedure the economic measures taken in the divorce judgment could be annulled. The protection of the weaker spouse was made even more complete by the recent ruling of the United Sections of the Supreme Court of 2021 that allowes the treatment of economic issues still pending, provided that the divorce decree between the parties was pronounced before the exequatur of the ecclesiastical sentence of marriage nullity.SOMMARIO: 1. Premessa - 2. I tratti salienti dell’attuale procedimento di delibazione - 3. La differente tutela del coniuge nel caso di nullità e di divorzio - 4. Il rapporto delibazione-divorzio tra tesi dottrinali e orientamenti giurisprudenziali dalla metà degli anni Ottanta alla fine degli anni Novanta - 5. Gli interventi della giurisprudenza di vertice su delibazione e divorzio a partire dal 2001 - 6. L’ulteriore passo in avanti della Cassazione: dopo il giudicato di divorzio è possibile la trattazione delle questioni economiche ancora pendenti anche se nelle more sia intervenuto l’exequatur della nullità canonica - 7. Conclusioni.